Impact of the cybersecurity system on information keeping: A study of selected tertiary institutions in the northwest of Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study examined the impact of cybersecurity policies on information protection in some of the tertiary institutions in the northwest of Nigeria. The research was conducted based on two research questions and the use of a descriptive survey design. The data used was primary data gathered by a structured questionnaire. The population of the study consists of 3,257 participants and 356 were sampled using Taro Yamane’s formula. The data gathered was analyzed by employing Z-test with the help of Statistical Package for the Social Sciences software. The findings revealed that the cybersecurity system has a notable consequence on staff information protection in the chosen tertiary institutions in northwest of Nigeria and that the cybersecurity system has a notable impact on students’ information (database) in the chosen tertiary institutions. From the analysis, the findings recommend that tertiary institutions should have effective and efficient cybersecurity to secure vital information in tertiary institutions.